Chronic Pain in Canada: Have We Improved Our Management of Chronic Noncancer Pain? - Aline Boulanger; Alexander J Clark; Pamela Squire; Edward Cui; GLA Horbay (Pain Research and Management)
BACKGROUND: Chronic noncancer pain (CNCP) is a global issue, not only affecting individual suffering, but also impacting the delivery of health care and the strength of local economies.